The Role of Proprotein Convertases in the Regulation of the Function of Immune Cells in the Oncoimmune Response - Rose, Mélanie; Duhamel, Marie; Rodet, Franck; Salzet, Michel (Frontiers in Immunology, 2021)
Proprotein convertases (PC) are a family of 9 serine proteases involved in the processing of cellular pro-proteins. They trigger the activation, inactivation or functional changes of many hormones, neuropeptides, growth factors and receptors. Therefore, these enzymes are essential for cellular homeostasis in health and disease. Nine PC subtilisin/kexin genes (PCSK1 to PCSK9) encoding for PC1/3, PC2, furin, PC4, PC5/6, PACE4, PC7, SKI-1/S1P and PCSK9 are known. The expression of PC1/3, PC2, PC5/6, Furin and PC7 in lymphoid organs such as lymph nodes, thymus and spleen has suggested a role for these enzymes in immunity. In fact, knock-out of Furin in T cells was associated with high secretion of pro-inflammatory cytokines and autoantibody production in mice. This suggested a key role for this enzyme in immune tolerance. Moreover, Furin through its proteolytic activity, regulates the suppressive functions of Treg and thus prevents chronic inflammation and autoimmune diseases. In macrophages, Furin is also involved in the regulation of their inflammatory phenotype. Similarly, PC1/3 inhibition combined with TLR4 stimulation triggers the activation of the NF-κB signaling pathway with an increased secretion of pro-inflammatory cytokines. Factors secreted by PC1/3 KD macrophages stimulated with LPS exert a chemoattractive effect on naive auxiliary T lymphocytes (Th0) and anti-tumoral activities. The link between TLR and PCs is thus very important in inflammatory response regulation. Furin regulates TL7 and TLR8 processing and trafficking whereas PC1/3 controls TLR4 and TLR9 trafficking. Since PC1/3 and Furin are key regulators of both the innate and adaptive immune responses their inhibition may play a major role in oncoimmune therapy. The role of PCs in the oncoimmune response and therapeutic strategies based on PCs inhibition are proposed in the present review.